Analyzing the Impact of Systematic Risk, Market Capitalization and Firm Size on the Financial Performance of Selected Companies Listed in SENSEX - Bhattacharyya, Sandip; Shaw, Vinay Kumar (International Journal of Engineering and Management Research, 2026)
Our Study evaluates that the impact of systematic risk, market valuation and firm size on the financial performance of selected Sensex companies. The objective of our study is to identify which factors most strongly influence annual stock returns and provide direction for investors and portfolio managers. In our study, data collected from 25 companies over the period 2021–2025 were analyzed using descriptive statistics, normality tests, correlation, regression and ANOVA analysis test. Descriptive analysis showed variation in total returns, risk measures and market valuation indicators. Normality tests confirmed the data distribution was suitable for further statistical analysis. Correlation results indicated weak to moderate relationships between financial performance and independent variables. Another statistical tool that is Regression analysis highlighted that firm size which is measured by market capitalization, has a significant negative effect on total annual return, whereas systematic risk, price-to-earnings ratio, and price-to-book value ratio were not significant predictors. ANOVA stated that there was no significant differences in returns across financial years, suggesting relative stability over time. In our study the findings suggest that firm size is a key determinant of stock performance in the Indian equity market. This study provides empirical evidence that can assist investors and portfolio managers in making informed decisions and prioritizing firm size when evaluating stock returns.